SPACE-RL Innovation Transfer Model “Science – Business” - Artem ARTYUKHOV; Svitlana BILAN; Iurii VOLK; Serhiy LYEONOV; Desislava SERAFIMOVA (European Journal of Interdisciplinary Studies, 2023)
The article deals with creating the innovation transfer model “science - production – business”. It is based on quantitative indicators for assessing the external environment and market analysis, the landscape for implementing the development and introduction of innovation and evaluating the internal environment and the level of readiness for implementation. The authors provide ways of commercializing the scientific research results and describe the role of an entrepreneurial university in achieving the main tasks of innovation and technology transfer. A combined SPACE-RL model for assessing the prospects for new scientific ”products” concerning external and internal influencing factors is proposed. The SPACE matrix, from a subjective assessment tool based on qualitative indicators determined by experts, has turned into a SPACE-RL model, in which it is possible to compare the entrepreneurial university's capabilities in terms of the strategy of bringing the invention to the market and the readiness of the invention to become innovation The SPACE-RL model maximally objectifies the innovation transfer process, reducing the influence of qualitative factors on decision-making.